A Methodology to Promote Deleterious Oral Habit Change through an Educational and Fun Game - Andrea Ferreira de Oliveira; Maria Andréia Formico Rodrigues; Isabel Magalhães Pinto Ribeiro (Revista Interacções, 2022)
Babies develop several reflexes to help them adjust to life outside the womb, and one of them is sucking. However, if persisting for more than three years after birth, deleterious oral habits can cause consequences such as inadequacy in positioning the jaws, lips, tongue and palate, among other health issues. This work presents a methodology to promote deleterious oral habit change through an educational game that encourages the child to abandon this habit in a conscious and consenting way. We created the narrative and developed the game to be played for seven consecutive days. It contemplates four phases of a learning player's journey. Moreover, this learning journey is enriched with four fun and challenging minigames. Each day, the player can experience new adventures and awareness activities to stimulate behaviour change spontaneously through positive reinforcement. Furthermore, we implemented a pointsbased rewards system to generate an impact on player satisfaction. Finally, our methodology also offers the opportunity to bring together the child's family and dental professional to act collaboratively in favour of health, offering the child confidence and the chance to explore the deleterious oral habit, learn, and change.